Pengembangan Usaha Mikro, Kecil, Dan Menengah (UMKM) Di Kelurahan Gebang Putih Melalui Fasilitas Internal Dan Eksternal - Dyta Rizky Tamara; Riko Setya Wijaya; M. Taufiq (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have the potential to drive community economic activities as well as being the source of income for most people in improving welfare, therefore to explore and encourage this potential it is necessary to analyze development through internal and external facilities. The purpose of this research is to find out, describe, and analyze the development of Micro, Small, and Medium Enterprises (MSMEs) in Gebang Putih Village through internal and external facilities and analyze problem factors in the development of MSMEs. The research method used in this research is descriptive analysis, which describes and describes the situation, conditions, or events observed, namely regarding the development of MSMEs in Gebang Putih Village through internal and external facilities. The data analysis stage in this research uses data collection, data reduction, data presentation and then conclusion drawing. The data that has been obtained in the field is then recorded and analyzed. The results of this study found that the development of MSMEs will not be successful if it only relies on internal facilities. The role of external parties as facilitators has not been maximized. These problems can be overcome with a maximum assistance program because if it is only in the form of coaching and training, it is feared that the knowledge gained is only like a breeze without any implementation in the real world, for example related to technological knowledge and innovation in production.